The effects of subsidies on foods in Iran: A narrative review - Saeediankia, Afsaneh; Majdzadeh, Reza; Haghighian-Roudsari, Arezoo; Pouraram, Hamed (Frontiers in Sustainable Food Systems, 2023)
Background Subsidy payments are used to support low-income groups and may improve income distribution and increase social welfare. The food subsidy programs and their long-term effects have been considered as major developmental issues in many developing countries. This review study aimed to examine the effects of subsidies on the food and nutritional status of Iranian people. Methods English and Persian language databases were searched using related keywords to discover studies on the effects of subsidies on food and nutritional status in Iran. A manual search was also conducted encompassing national and local research projects in Iran. In total, 12 articles were finally included out of an initial total of 70 studies. Results Subsidy payment affects many socio-economic variables. In Iran, subsidies are often paid for the basic goods and commodities that are a main part of the consumption patterns of most Iranian people. So, if the basic needs of the people are not well-understood, changes in economic structures may lead to a change in consumption patterns. In addition, physical payments for food may lead to an increase in the consumption of different groups, but cash payments do not necessarily lead to an increase in food intake. Conclusion The method of payment should be chosen correctly to improve the protection of vulnerable populations. The distribution of targeted subsidies for food security is inevitable due to limited resources available to support vulnerable populations.